Pelaksanaan Pendidikan untuk Pembangunan Berkelanjutan oleh Beberapa Lembaga - Nur Listiawati (Jurnal Pendidikan dan Kebudayaan, 2013)
The objective of the study is to identify the role and the pursuit of educational institutions in disseminating and implementing the concept of sustainable development. The study is a research field that uses a qualitative approach to obtain information about the program developed by institutions and itsâ€™ scope, as well as its application in the educational unit that covers targets of the program and investment strategies on the value of each program. The study showed that coverage of the value of education for sustainable development are implemented and embedded in the education unit is still largely focused on environmental perspective and targets of each program varied, mostly are educators, learners and principals; strategy in instilling of values diversÂ  e including integration to subjects of learning, local content, extracurricular, habituation, and familiarization, that most people do it through integration and habituation and acculturation.